2021
DOI: 10.3390/agronomy11091682
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Symptomatic Disease Detection in the Vine, Chrysanthemum, and Rose Leaves with a Low-Cost Infrared Sensor

Abstract: Thermography is a technique based on infrared imaging, which is used nowadays to detect plants under stress caused by biotic and abiotic factors. In many cases, temperature changes have already been correlated with pathogen attacks. In this sense, thermography offers the ability of early disease detection in plant pathology. In this work, a low-cost AMG8833 Grind-Eye infrared camera combined with a 1080P RGB web camera was used to develop an integrated infrared and RGB imaging system, to record temperature cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…It is unknown whether infrared or other spectrums could be used to effectively detect hop latent viroid; limited research has been carried out on virus detection with infrared, but there may be potential applications [ 129 , 130 ]. Vagelas et al [ 131 ] utilized a low-cost infrared camera and a standard RGB web camera to analyze vine, chrysanthemum and rose leaves that had been infected with various fungi. Results showed that infected leaves exhibited temperature deviations from uninfected ones, which occurred before visible symptoms developed.…”
Section: Cannabis Pathogens: Symptoms and Management Approaches At Di...mentioning
confidence: 99%
“…It is unknown whether infrared or other spectrums could be used to effectively detect hop latent viroid; limited research has been carried out on virus detection with infrared, but there may be potential applications [ 129 , 130 ]. Vagelas et al [ 131 ] utilized a low-cost infrared camera and a standard RGB web camera to analyze vine, chrysanthemum and rose leaves that had been infected with various fungi. Results showed that infected leaves exhibited temperature deviations from uninfected ones, which occurred before visible symptoms developed.…”
Section: Cannabis Pathogens: Symptoms and Management Approaches At Di...mentioning
confidence: 99%